Incident wavelength resolved resonant SERS on au sphere segment void (SSV) arrays - Tognalli, Nicolas Gerardo (2012)
Sphere segment void (SSV) arrays allow the reproducible engineering of plasmon-polariton modes from the near-infrared to the ultraviolet through the tuning of the void height and diameter. The wavelength dependence of surface-enhanced Raman scattering (SERS) can then in principle be controlled by selecting these parameters. Using 4-mercaptopyridine as a covalently bonded nonresonant molecular probe, we report a detailed study of such wavelength dependence of SERS in Au SSV arrays as a function of void diameter and height. We conclude that the SERS mechanism on SSV arrays depends on the plasmonic properties of the substrates and also that additional effects contribute significantly to the observed enhancement including a chemical contribution related to the molecular probe and a nanostructuring induced surface plasmon localization existent for the smaller cavity dimensions. © 2012 American Chemical Society.